THE EFFECT OF MOTIVATION TOWARD EFL LEARNERS’ ENGLISH READING SKILL ACHIEVEMENT - Kawakiby, Ihza Noval; St. Shabibatul Rohmah; Rizki Nurfida Pambayun (Universitas PGRI Palembang, 2025)
This study investigates how intrinsic and extrinsic motivation affect the reading performance of third-grade EFL students at Al Kautsar Putra Secondary School. Using a qualitative approach, data were gathered from questionnaires, interviews, and academic records. The questionnaire, with